CD4+ Th1 and Th17 responses and multifunctional CD8 T lymphocytes associated with cure or disease worsening in human visceral leishmaniasis - de Franca, Mariana Nobre Farias; Rodrigues, Lorranny Santana; Barreto, Aline Silva; da Cruz, Geydson Silveira; Aragão-Santos, José Carlos; da Silva, Angela Maria; de Jesus, Amélia Ribeiro; Palatnik-de-Sousa, Clarisa B.; de Almeida, Roque Pacheco; Corrêa, Cristiane Bani (Frontiers in Immunology, 2024)
to answer to the requirements of the 3 reviewers, the Abstract of the revised manuscript has now more than 350 words. Since it exceeds the limit of this window, please see the abstract in the Word and PDF files fo the Revised manuscript with tracked changes.